Impact of Fuel Subsidy Removal on Gross Domestic Product and Transportation Cost in Nigeria - Olusegun, O.A.; Afolabi, Q.B.; Ogola, D.B. (European Journal of Theoretical and Applied Sciences, 2023)
This study identified economic problem arising from transportation cost due to removal of fuel subsidy in Nigeria. We therefore decided to collect secondary data from Statista, World Bank web link and prices of Premium Motor Spirit (PMS) from 2011-2023. Data on the three variables i.e GDP, the price of PMS and inflation rate were correlated to determine their level of relationships. Pearson Product Moment Correlation Coefficient was used to analyse the secondary data with the aid of SPSS software. The result from the analysis indicated that, inflation increased by 64% with increased fuel price decreasing GDP by 42.5%. Inflation is witnessed to have increased and GDP decreases. It can be seen that fuel is very critical to the development of Nigeria. It has a direct effect on GDP and surprisingly price inflation has impact on Nigerians. Solving one problem perhaps of fuel has a significant effect on economy. There are two things that should be done as alternatives to subsidy removal; the first is to make the supply of fuel more than the demand. The second option is to find alternative fuel like other countries because the demand for crude oil as major revenue may dwindle over time if the buyers who are planning vigorously on alternative fuel are able to do away with our crude oil. The use of electric vehicle, solar powered vehicles, hybrid vehicles and policy that will encourage non motorized transport can assist Nigeria to forestall future challenges of global oil demand.
This study identified economic problem arising from transportation cost due to removal of fuel subsidy in Nigeria.
Keywords: Fuel; Transportation; GDP; Nigeria; Subsidy.